Anorectal manometry in disorders of defecation: a retrospective study - Raman, Vinod Kumar Reddy; Bagepally, Ravi Shankar; G. R., Srinivas Rao; Donapati, Viswanath Reddy; Adi, Rakesh Kumar; Reddy, Vamshidhar; Mannava, Anil Kumar; Jogu, Kiran Kumar; Bongu, Shruti Sagar (International Journal of Research in Medical Sciences, 2025)
Background: Prevalence of Chronic Constipation (CC) in India is around 12-30%. Diagnosis of Fecal Evacuation Disorder (FED) requires specialized investigations like Anorectal Manometry (ARM), Balloon Expulsion Test (BET), MR defecography. High resolution ARM is considered first line diagnostic tool for chronic constipation as it measures pressure exerted by the muscles of anus and rectum. This study aimed to evaluate the characteristics of anorectal pressure in a cohort of Indian patients with CC and fecal incontinence and types of FED in patients with CC and age distribution (in young and elderly). Methods: The present retrospective study was conducted from January 2022 to May 2024 at department of gastroenterology, Yashoda hospitals, Secunderabad, India. A total of 266 patients who presented with CC or Fecal incontinence were included in the study. Sigmoidoscopy or full-length colonoscopy, BET and ARM were done in all the patients. Mean resting and squeeze pressure and other parameters were measured by ARM. Data was compiled and observations tabulated. Results: Among 266 patients, 136 were young with mean age 21.93±10.54 years and 130 with mean age 60.43±11.87. Gender distribution was 59% men and 41% women. Mean resting anal pressure was 57.06±23.11 mg, mean squeeze pressure was 98.36±35.96 mmHg. In present study, type I dyssynergic defecation was most common with 76 (29%) patients followed by type II 46 (17%). Conclusions: The present study showed that 65% with constipation subjected for ARM had dysynergic defecation (DD) and type I DD was most common followed by type II. Similar trend was observed in both young and elderly patients.